Prominences of Rhymes' Role in Persian Poetry from the Beginning to the Eighth century - Tahereh Ghasemi; ali mohammadi (مطالعات زبانی و بلاغی)
The rhyme has always been one of the main pillar of Persian poetry. For that matter, poets spend many times to make rhyme and accentuate it. From the initial centuries of Persian poetry to the present time, many changes have been happen in rhymes. Some rhymes in the poems of some poets that have existed for a certain time and have not been used thereafter, “Emaleh” and “Dal-zal” are examples of these rhymes. Making rhymes to “Momal” words are not specify to Arabic words and are also used in Persian terms. But most of these rhymes are Arabic, which are matched with unknown “ya”. “Emaleh” Rhymes in the early periods of Persian poetry are few; but in the following periods they have increased. These Rhymes and “dal-zal” rhymes used until eight centuries. In Dahl-Zal rhymes, "Persian zal" and "Arabic zal" rhyme together. In the following periods, there is some changes in the pronunciation of these Persian words, and all of “mojame-zal” change into “mohmale-dal”. The pronunciation of the “Arabic-zal” remains, and through these types of arguments, we understand that the pronunciation of a “Persian-zal”, is similar to Arabic or has the same pronunciation. Another case is, study of the changes that poets make in the rhymes. Poets such as Sanaie, Molavi and Saadi have been more educated in this regard, and Molavi is one of the most prominent. This article examines these cases in the poetries of Persian poets from the fourth century to the eighth century, which is the period of growth and development of Persian poetry.